The effects of lead sources on oral bioaccessibility in soil and implications for contaminated land risk management. (March 2015) - Palmer, Sherry; McIlwaine, Rebekka; Ofterdinger, Ulrich; Cox, Siobhan F.; McKinley, Jennifer M.; Doherty, Rory; Wragg, Joanna; Cave, Mark
Abstract: Lead (Pb) is a non-threshold toxin capable of inducing toxic effects at any blood level but availability of soil screening criteria for assessing potential health risks is limited. The oral bioaccessibility of Pb in 163 soil samples was attributed to sources through solubility estimation and domain identification. Samples were extracted following the Unified BARGE Method. Urban, mineralisation, peat and granite domains accounted for elevated Pb concentrations compared to rural samples. High Pb solubility explained moderate-high gastric (G) bioaccessible fractions throughout the study area. Higher maximum G concentrations were measured in urban (97.6 mg kg −1 ) and mineralisation (199.8 mg kg −1 ) domains. Higher average G concentrations occurred in mineralisation (36.4 mg kg −1 ) and granite (36.0 mg kg −1 ) domains. Findings suggest diffuse anthropogenic and widespread geogenic contamination could be capable of presenting health risks, having implications for land management decisions in jurisdictions where guidance advises these forms of pollution should not be regarded as contaminated land. Highlights: Urban, mineralisation, peat and granite sources accounted for elevated Pb in soil. Pb solubility was higher in urban and mineralisation domains. Higher Pb solubility resulted in high oral bioaccessibility compared to rural areas. Diffuse background and natural Pb contamination could pose human health risks. Contaminated land policy should not dismiss diffuse or geogenic pollution sources. Abstract : Diffuse and widespread Pb sources displayed high oral bioaccessibility, providing implications for contaminated land risk assessment guidance that excludes these forms of pollution.